2019
DOI: 10.1016/j.cell.2019.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Shared Cortex-Cerebellum Dynamics in the Execution and Learning of a Motor Task

Abstract: Graphical Abstract Highlights d First simultaneous recordings from neocortex and cerebellum over weeks of learning d Cortical layer 5 and cerebellar granule cells show similar task encoding in experts d Learning increases correlations among initially dissimilar L5 and granule cells d L5 and granule cells converge to similar, low-dimensional, task-encoding activity Correspondence mjwagner@stanford.edu (M.J.W.), mschnitz@stanford.edu (M.J.S.), lluo@stanford.edu (L.L.) In BriefSimultaneous recordings of ensembles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
156
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(200 citation statements)
references
References 56 publications
26
156
1
Order By: Relevance
“…Leveraging the capabilities of our miniscope, we demonstrate functional interactions between the cerebellum and cortex in unrestrained mice wearing dual miniscopes. Complex spike activity in Purkinje cell dendrites correlated with cellular activity measured in the cortex during periods of movement, in line with previous anatomical and functional studies of cerebello-thalamo-cortical connectivity (Badura et al 2018;Bostan, Dum, and Strick 2013;Akkal, Dum, and Strick 2007;Hoover and Strick 1999;Gao et al 2018;Wagner et al 2019) . Moreover, activity correlated across regions typically preceded behavioral acceleration.…”
Section: Introductionsupporting
confidence: 87%
“…Leveraging the capabilities of our miniscope, we demonstrate functional interactions between the cerebellum and cortex in unrestrained mice wearing dual miniscopes. Complex spike activity in Purkinje cell dendrites correlated with cellular activity measured in the cortex during periods of movement, in line with previous anatomical and functional studies of cerebello-thalamo-cortical connectivity (Badura et al 2018;Bostan, Dum, and Strick 2013;Akkal, Dum, and Strick 2007;Hoover and Strick 1999;Gao et al 2018;Wagner et al 2019) . Moreover, activity correlated across regions typically preceded behavioral acceleration.…”
Section: Introductionsupporting
confidence: 87%
“…Choice-specific information has been observed across multiple regions of cortex (Feierstein et al, 2006;Harvey et al, 2012;Guo et al, 2014b;Li et al, 2015;Driscoll et al, 2017;Wagner et al, 2019). Similarly, we found that many vmPFC cells exhibited activity selective not only for the task epoch, but also for left or right choice directions ( Figures 6A, S6D).…”
Section: Vmpfc→pag Neurons Contain the Most Information About Choice supporting
confidence: 72%
“…Primary motor cortex activity is also modified during motor learning in the context of self-initiated reaching (Sanes and Donoghue, 2000;Li et al, 2001;Diedrichsen et al, 2005;Kawai et al, 2015) , though, to our knowledge, no studies have definitively linked primary motor cortex to the learning process itself. Another likely common node, especially for the learning process, is the cerebellum, which is richly interconnected with primary motor cortex (Wagner et al, 2019) . Cerebellar circuits are strongly implicated in multi-joint coordination during both feedforward control and feedback responses (Holmes, 1939;Goodkin et al, 1993;Bastian et al, 1996Bastian et al, , 2000Kurtzer et al, 2013;Wagner et al, 2019) and have long been hypothesized to house the computations related to internal models (Wolpert et al, 1998;Kawato, 1999) .…”
Section: Internal Models For Feedback Controlmentioning
confidence: 99%
“…Another likely common node, especially for the learning process, is the cerebellum, which is richly interconnected with primary motor cortex (Wagner et al, 2019) . Cerebellar circuits are strongly implicated in multi-joint coordination during both feedforward control and feedback responses (Holmes, 1939;Goodkin et al, 1993;Bastian et al, 1996Bastian et al, , 2000Kurtzer et al, 2013;Wagner et al, 2019) and have long been hypothesized to house the computations related to internal models (Wolpert et al, 1998;Kawato, 1999) .…”
Section: Internal Models For Feedback Controlmentioning
confidence: 99%